METODE BUZZ GROUP DISERTAI MEDIA KELERENG SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SD NEGERI 023898 BINJAI UTARA - Sufriati Sufriati (MES: Journal of Mathematics Education and Science, 2017)
This study aims to find out how to improve the results of mathematics learning on the subject of summing in integers through Buzz Group method along with media Kelereng on the students of class I SD Negeri 020580 Binjai. And how the creativity and ability of teachers in implementing learning in the classroom. The result of this research concludes that the result of student learning in learning through Buzz Group method is On cycle I the good categorization value reaches only 20%. That means that a small part of the first cycle is more increased than before the improvement of learning. Nevertheless, the less categorized students are still in the most process that is 40% and the categorized is as much as 40% that finally in the second cycle the number of students who are categorized moderate and less should decrease. In cycle II, good categorized value is much more and melngalami significant achievement increase that reaches 80%. then the students who get the category is 20%. After the main problems in the improvement of learning on the cycle I and II implemented, the authors were satisfied with the increase in student value on the implementation of improvement learning in cycle II seen in the moderate category decreased and the absence of students who got less value